Apologetics: A Justification For Contemporary Christian Beliefs - Mamosey, Tammy; Maramis, Fetrie JL (Jurnal Indonesia Sosial Sains, 2025)
The creation of this article is a collaboration between lecturers and students in carrying out the teaching and learning process at the Global Glow Indonesia College (STTGGI) Jakarta. Lecturers are in Jakarta, while students live in the USA. This article discusses the relevance and application of Christian apologetics in contemporary contexts, focusing on the presuppositional approach taken by John M. Frame. Apologetics, as a discipline that defends and justifies the Christian faith, is often confronted with modern intellectual and cultural challenges. Frame offers a unique framework, one that rejects autonomous neutrality and instead asserts the supremacy of divine revelation as the basis for all knowledge. The presuppositional approach argues that a person's basic assumptions, or "presuppositions," fundamentally shape how they understand and evaluate truth claims. For Frame, God's revealed truth in the Bible is a key presupposition that must be recognized before any rational discussion can proceed meaningfully. This article will explore how Frame's views provide a solid foundation for responding to criticism of the Christian faith, including questions about the existence of God, evil, science, and morality. By highlighting the limitations of autonomous rationalism and the need for a transcendent starting point, Frame invites apologists not only to defend the faith, but also to show that the Christian worldview is the only coherent framework that can adequately explain reality. This study uses a qualitative method, analyzing Frame's key works and their application in current apologetic discourse, to identify practical implications for churches and individuals in the face of contemporary challenges to Christian belief. This article aims to present a comprehensive understanding of Framean apologetics as a vital tool for the vindication of the Christian faith in the 21st century, emphasizing the need for dependence on God and His revelation as the foundation for all intellectual endeavors.